Design Information System Accounting Sales Website-Based (Case Study: PT Arbunco Wira Pandega) - Yulandha, Nadia; Saputro, Janu Ilham; Nissa, Nadia Khaerun (APTISI Transactions on Management (ATM), 2020)
Arbunco Wira Pandega does not have a system that covers all activities, one of which is in the sales department and the financial section in making sales reports and financial reports are still manually using Microsoft. Excel so that the media used are still very likely to cause human error so a sales accounting system is needed so that it can produce sales reports and financial reports that are more effective and efficient in the process of making sales reports and financial reports. This research uses the SWOT analysis method, PIECES, system requirements elicitation, and system modeling using UML (Unified Modeling Language) to visualize, which is then implemented with the Hypertext Preprocessor (PHP) programming language with the MySQL-Server database as the database used . With the sales accounting system, it can simplify the sales department and the finance department to produce accurate sales and financial reports in a fast time, so as to create effective and efficient performance, and can support evaluation in internal control for the leadership of the report.